Students’ Vocabulary Competence at the Seventh Grade of Junior High School - Budiarti Putri Uleng; Nadya Nurhidayah Nurdin; Musyrifah Mahfuddin; Mimma Wandasari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aimed to examine the vocabulary competence of seventh-grade students at SMPN Satap Pongsamelung. The population consisted of 61 students, from which 29 students were selected through random sampling. A descriptive quantitative research design was employed, and data were collected using a multiple-choice vocabulary test. The results revealed that the highest score obtained by the students was 88, while the lowest score was 19, with a mean score of 55.62. Based on the classification criteria, students’ vocabulary competence was categorized as poor. These findings indicate that students still face difficulties in mastering English vocabulary, highlighting the need for improved instructional strategies to enhance vocabulary learning outcomes.